DOI: 10.1007/978-3-540-73460-4_36
|View full text |Cite
|
Sign up to set email alerts
|

Increase ICT Project Success with Concrete Scope Management

Abstract: With the Standish group's CHAOS report proclaiming ICT project success on a mere one-third of projects, project managers have an obligation worldwide to gain control of the situation. Through concrete scope management processes, ICT project managers can learn and embrace proven approaches that measure the size of software projects, streamline the requirements articulation and management, and impose solid change management controls, to keep projects on time and on budget. Scope management is not rocket science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…Scope management is defined as a key knowledge area within the PMBoK ® and is positioned as being a core component of project success (PMI 2014). The literature supports the link between project success, the formal management of requirements and project scope (Dekkers and Forselius 2007;Parsons-Hann and Liu 2005;Tamai and Kamata 2009).…”
Section: Management Of Scopementioning
confidence: 84%
“…Scope management is defined as a key knowledge area within the PMBoK ® and is positioned as being a core component of project success (PMI 2014). The literature supports the link between project success, the formal management of requirements and project scope (Dekkers and Forselius 2007;Parsons-Hann and Liu 2005;Tamai and Kamata 2009).…”
Section: Management Of Scopementioning
confidence: 84%
“…Incomplete information stifles project progress and project success (Babar, Ghazali & Jawawi 2014;Dekkers & Forselius 2007;Marnewick 2013). …”
Section: Uncertaintymentioning
confidence: 99%
“…empirically and statistically [29][30][31][32][33][34][35][36]. The studies showed that various factors like Management commitment, financial constraints, organisational structure, reward system, education and training of project teams play a crucial role in the successful management of projects.…”
Section: Overview Of Related Researchmentioning
confidence: 99%